Combined impact of summer NAO and northern Russian shortwave cloud radiative effect on Eurasian atmospheric circulation - Liu, Le; Wu, Bingyi; Ding, Shuoyi (Environmental research letters, 2023)
Based on ERA-Interim and CERES_SYN1deg Ed4.1 datasets, the combined influence of summer North Atlantic Oscillation (SNAO) and positive shortwave cloud radiative effect (SWCRE) events in northern Russia on Eurasian atmospheric circulation is investigated at the intraseasonal scale. The impact of the SNAO on the position of the North Atlantic storm track is modified combined with the Ural anticyclone anomaly contributed by positive northern Russian SWCRE anomalies, which could affect the summer stationary wave pattern. During positive northern Russian SWCRE events under SNAO+, the upstream wave train enhanced by the southward Ural anticyclone anomaly is easily trapped by the northward South Asian jets, thus propagating to low latitudes and causing extreme heat events in East Asia. Under SNAO-, the wave train propagates in the British–Baikal Corridor pattern along polar front jet towards the Far East, slowing down the dramatic melting of sea ice in the Laptev and East Siberian seas. Summer positive SWCRE events in northern Russian act as a bridge by promoting the emergence of the Ural anticyclone anomaly, influencing extreme weather in East Asia and Arctic sea ice variability.